Assessment of Risk Factors for 30-Day Hospital Readmission After Surgical Cytoreduction in Epithelial Ovarian Carcinoma. Issue 5 (1st July 2011) - Fauci, Janelle M.; Schneider, Kellie E.; Frederick, Peter J.; Wilding, Gregory; Consiglio, Joe; Sutton, Amelia L.; Kilgore, Larry C.; Barnes, Mack N.
Abstract : Objective: To evaluate factors that place epithelial ovarian cancer (EOC) patients at increased risk for hospital readmission. Methods: A retrospective review of patients diagnosed with EOC undergoing surgical cytoreduction at the University of Alabama at Birmingham from 2001 to 2008 was performed. Patients who required readmission were identified. Demographic data, comorbidities, surgical data including bowel resections, and hospital length of stay were evaluated. Results: A total of 207 patients were identified. The mean age at diagnosis was 64 years (range, 32-89 years), 58% had optimal debulking (n = 120), and the mean number of comorbidities was 1.3 (range, 0-6). Readmission within 30 days of discharge occurred in 33 (16%) of 207 patients. The readmission group had a statistically higher number of comorbidities (1.75 vs 1.01, P = 0.025). The most common reasons for readmission were small bowel obstruction/ileus, wound complications, and thromboembolic events. Conclusions: The most common reason for readmission after cytoreductive surgery for EOC is small bowel obstruction/ileus. Studies assessing postoperative disease management programs including nursing telephone follow-up, administration of outpatient intravenous fluids, and continuation of antithrombotic agents may offer opportunities to reduce readmissions.